Pengaruh Problem Based Learning dengan Mind Mapping Terhadap Keterampilan Berpikir Kritis - Wahyu Rikha Rofikhatul Ula (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2019)
This research is motivated by critical thinking skills of elementary students who are low especially in learning science. The problem raised in this study is is there a difference in the critical thinking skills of students who learn to use PBL models with mind mapping and students who learn to use interactive lecture methods. This study uses a quantitative method of quasi-experimental form and the design of the control group and the experimental group. The population consisted of 6 schools, then samples were taken by means of selected purposive sampling SDN 4 Puyoh and SDN 5 Puyoh, then randomization was carried out to determine the control group and the experimental group. SDN 5 Puyoh was chosen as the experimental group and SDN 4 Puyoh as the control group. The results of this study are; (1) there is an increase in students' critical thinking skills between before and after learning carried out both in the control group and the experimental group; and (2) there was a significant increase in the critical thinking skills of elementary school students in the experimental group, namely the group using PBL learning with mind mapping compared to students in the control group who followed the learning with interactive lecture methods.